Motivation and Stress Management: Essential Skills for Parents, Teachers and Students - Ahmad, Jasim (JOURNAL OF INDIAN EDUCATION, 2009)
Nowadays it is frequently heard that people of different age including students commit suicide due to several reasons. It is generally found that individuals commit suicide either due to non-achievement of the desired goals or due to the firm faith in failure. The author has the opinion that it is solely because of the mismanagement of motivation and stress. In this article an attempt is made to elaborate the role of motivation and stress in an individual’s life and the management of the same.